The Effect of Tongue Twister Technique on Students’ Pronunciation Consonant /ð/ and /θ/ Sounds - Astuti, Uci; Nurnia, Nurnia; Muhsin, Muhammad Khusnun (Universitas Halu Oleo, 2021)
Pronunciation is one of the micro skills of speaking that has to learn by students. The lack of teacher’s attention in teaching pronunciation, caused students lack confidence to speak English. This research aimed to find out the effectiveness of using Tongue Twister Technique on students’ English pronunciation. This research used pre-experimental with One-Group Pretest-Posttest design. The sample of this research was class XI IPA 1 consisted of 12 students which had been selected by using simple random sampling. The instrument of this research was reading aloud test (oral test) which focused on consonant /ð/ and /θ/ sounds, and the test from the text book that used by the teacher in teaching English in the classroom. The researcher collected the data by giving a pre-test and post-test in order to know students’ pronunciation ability before and after treatment of tongue twister technique. Then, the researcher used SPSS 16.0 to analyze the data of this research. The finding shows that tongue twister technique has an effect on students’ pronunciation, especially in pronouncing consonant /ð/ and /θ/ sounds. It might be influenced of several factors such as using media in teaching English pronunciation and students’ motivation, and students’ interest toward using technique in teaching pronunciation.